POSITIVE PRACTICES OF DEVELOPING DIGITAL COMPETENCE OF ACADEMIC STAFF OF HIGHER EDUCATION INSTITUTIONS: EXPERIENCE OF THE PEOPLE’S REPUBLIC OF CHINA - Sergeieva, Larysa; Muranova, Nataliia; Kupriyevych, Viktoriya (Professional Pedagogics, 2022)
The relevance of the study is due to the need for developing the digital competence of teachers in higher education institutions at the international level. The objective is to describe and substantiate positive practices of developing the digital competence of academic staff in higher education institutions of the People’s Republic of China to use the positive experience of this country in reforming Ukrainian education. Methods: theoretical analysis of scientific sources, websites of educational institutions, and educational and professional programmes and working curricula for the competence development of academic staff to determine the main positive trends in developing digital competence of academic staff in higher education institutions of the People’s Republic of China. Results: the concept of digital competence is formulated and clarified and the issue of forming digital competence in representatives of higher education from different countries of the world, as well as relevant research on its development in the academic staff of higher education institutions, are analysed. The measures for the implementation of digital education in the PRC are characterised and proposals are formulated to solve the issue of developing digital competence and information literacy of teachers in higher education institutions. Conclusions: it has been found that the development of digital competence of Chinese teachers is more effective in creative activities. It has been determined that improving the control of interactive learning by college and university managers, improving the timeliness of feedback and interaction between teachers and students in the learning process, enriching the variety of interactive forms and means of improving the efficiency and effectiveness of learning, highlighting the best online courses and programmes to organise experience exchange events for academic staff of higher education institutions, ensuring that higher education institutions participate in training, workshops, seminars and other forms of scientific interaction are the effective means of developing the level of digital competence and information literacy of teachers in higher education institutions.